Daylight-adaptive lighting control techniques: a comparative analysis of particle swarm optimization and firefly algorithm - Wagiman, Khairul Rijal; Md Adnan, Mohd Faiz; Hussin, Imran; Md Nor, Mohd Hairwan; Din, Asri (2024)
Lighting in commercial buildings consumes a substantial amount of energy. Therefore, this paper developed particle swarm optimization (PSO) and firefly algorithm (FA) as control techniques for lighting systems to improve energy efficiency and satisfy occupantsꞌ visual comfort in an indoor environment. An office room was considered to test the performance of the PSO and FA techniques. The proposed methods showed superior performance in minimizing the cost of energy consumption by more than 60% while satisfying illuminance-based metrics mentioned by the European Standard EN 12464-1. Based on the comparative result, PSO outperformed FA by 3% in energy savings. Due to its performance, the proposed PSO method can be utilized for other types of buildings